Factors governing long‐term adherence to a gluten‐free diet in adult patients with coeliac disease. Issue 6 (23rd July 2015) - Villafuerte‐Galvez, J.; Vanga, R. R.; Dennis, M.; Hansen, J.; Leffler, D. A.; Kelly, C. P.; Mukherjee, R.
Summary Background A strict gluten‐free diet is the cornerstone of treatment for coeliac disease. Studies of gluten‐free diet adherence have rarely used validated instruments. There is a paucity of data on long‐term adherence to the gluten‐free diet in the adult population. Aims To determine the long‐term adherence to the gluten‐free diet and potential associated factors in a large coeliac disease referral centre population. Methods We performed a mailed survey of adults with clinically, serologically and histologically confirmed coeliac disease diagnosed ≥5 years prior to survey. The previously validated Celiac Disease Adherence Test was used to determine adherence. Demographic, socio‐economic and potentially associated factors were analysed with adherence as the outcome. Results The response rate was 50.1% of 709 surveyed, the mean time on a gluten‐free diet 9.9 ± 6.4 years. Adequate adherence (celiac disease adherence test score <13) was found in 75.5% of respondents. A higher level of education was associated with adequate adherence (P = 0.002) even after controlling for household income (P = 0.0220). Perceptions of cost, effectiveness of the gluten‐free diet, knowledge of the gluten‐free diet and self‐effectiveness at following the gluten‐free diet correlated with adherence scores (P < 0.001). Conclusions Long‐term adherence to a gluten‐free diet was adequate in >75% of respondents. Perceived cost remains a barrier to adherence. Perceptions of effectiveness of gluten‐free diet as well as its knowledge, are potential areas for intervention.